The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/app13116654
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anticancer Activity of Organic Kimchi with Starters Demonstrated in HT-29 Cancer Cells

Abstract: This study aims to investigate the effects of kimchi made with organic ingredients and lactic acid bacteria (LAB) as starters (Leuconostoc mesenteroides + Lactiplantibacillus plantarum) on HT-29 human colon carcinoma cells. Four types of kimchi (standard kimchi (SK), commercial kimchi (CK), anticancer kimchi (AK), and organic anticancer kimchi (OAK)) were evaluated. The results show that, among the different types of kimchi studied, OAK presents high DPPH free-radical scavenging activity and total phenol and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A Wallac Victor3 1420 Multilabel Counter (Perkin-Elmer, Wellesley, MA, USA) was used to detect absorbance at 765 nm. The standard curve was created with gallic acid as the reference (standard concentration was 0.03125-1 mg/mL), and it was used to quantify the TP content of broccoli [25].…”
Section: Assessment Of Total Phenol (Tp) Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…A Wallac Victor3 1420 Multilabel Counter (Perkin-Elmer, Wellesley, MA, USA) was used to detect absorbance at 765 nm. The standard curve was created with gallic acid as the reference (standard concentration was 0.03125-1 mg/mL), and it was used to quantify the TP content of broccoli [25].…”
Section: Assessment Of Total Phenol (Tp) Contentmentioning
confidence: 99%
“…Then, dispense 20 µL of 1 N NaOH with vortexing and heat the block for 1 h at 37 • C. The absorbance at 420 nm was measured using a Wallac Victor3 1420 Multilabel Counter. The flavonoid content was determined using the standard calibration curve generated by drawing the standard curve with Quercetin (Sigma-Aldrich Co., St. Louis, MO, USA) as the reference (standard concentration is 0-1280 µg/mL) [25].…”
Section: Assessment Of Total Flavonoid (Tf) Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that fermented cruciferous vegetables have an anti-cancer effect, possibly related to the anti-cancer value of cruciferous vegetables being preserved after pickling based on in vitro experiments. A series of studies proved that kimchi could inhibit the proliferation of HT-29 colon cancer cells [ 94 , 95 ]. Studies showed that fermented mustard leaf does not affect normal colon myofibroblast CCD-18Co cells but can terminate the proliferation of HCT116 cancer cell lines and lead to large-scale cell apoptosis.…”
Section: Health Benefits Of Fermented Vegetablesmentioning
confidence: 99%
“…Researchers have utilized HT-29 cells to examine the effects of manipulating Bcl-2 expression or activity on the behaviour and treatment response of colorectal cancer cells. Studies [36,37] have demonstrated that downregulating or inhibiting Bcl-2 in HT-29 cells can lead to enhanced apoptosis and reduced cell viability. This suggests that targeting Bcl-2 can sensitize HT-29 cells to apoptosis and potentially improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%